Deep silicon maxima in the stratified oligotrophic Mediterranean Sea - Y. Crombet; K. Leblanc; B. Quéguiner; T. Moutin; P. Rimmelin; J. Ras; H. Claustre; N. Leblond; L. Oriol; M. Pujo-Pay (Biogeosciences, 2011)
The silicon biogeochemical cycle has been studied in the Mediterranean Sea during late summer/early autumn 1999 and summer 2008. The distribution of nutrients, particulate carbon and silicon, fucoxanthin (Fuco), and total chlorophyll-a (TChl-a) were investigated along an eastward gradient of oligotrophy during two cruises (PROSOPE and BOUM) encompassing the entire Mediterranean Sea during the stratified period. At both seasons, surface waters were depleted in nutrients and the nutriclines gradually deepened towards the East, the phosphacline being the deepest in the easternmost Levantine basin. Following the nutriclines, parallel deep maxima of biogenic silica (DSM), fucoxanthin (DFM) and TChl-a (DCM) were evidenced during both seasons with maximal concentrations of 0.45 μmol L−1 for BSi, 0.26 μg L−1 for Fuco, and 1.70 μg L−1 for TChl-a, all measured during summer. Contrary to the DCM which was a persistent feature in the Mediterranean Sea, the DSM and DFMs were observed in discrete areas of the Alboran Sea, the Algero-Provencal basin, the Ionian sea and the Levantine basin, indicating that diatoms were able to grow at depth and dominate the DCM under specific conditions. Diatom assemblages were dominated by Chaetoceros spp., Leptocylindrus spp., Pseudonitzschia spp. and the association between large centric diatoms (Hemiaulus hauckii and Rhizosolenia styliformis) and the cyanobacterium Richelia intracellularis was observed at nearly all sites. The diatom's ability to grow at depth is commonly observed in other oligotrophic regions and could play a major role in ecosystem productivity and carbon export to depth. Contrary to the common view that Si and siliceous phytoplankton are not major components of the Mediterranean biogeochemistry, we suggest here that diatoms, by persisting at depth during the stratified period, could contribute to a large part of the marine primary production as observed in other oligotrophic areas.